Synthesis and characterization of electrical conducting chitosan-graft-polyaniline (eXPRESS Polymer Letters, 2007)
A mucopolysaccharide, chitosan was grafted with polyaniline through oxidative-radical copolymerization using ammonium persulfate in acidic medium. The grafting conditions were extensively studied by varying grafting parameters. All the findings have been discussed and proposed a plausible mechanism for the graft copolymerization. The representative chitosan-graft-polyaniline (Ch-g-PANI) was characterized using UV-vis, FTIR, TGA, X-ray diffraction and Scanning electron microscopy taking chitosan as reference. Ch-g-PANI exhibited electrical conductivity, which increases with the extent of grafting onto chitosan backbone. Its electrical conductivity is further influenced by pH and showed pH switching electrical conduction behavior when exposed to NN3/HCl vapors. The application of conducting biomaterial such as Ch-g-PANI in the electronic devices especially for the fabrication of sensor devices would be attractive not only in terms of product cost and environmental safety but also from a materials science point of view.